Researching Professionals or Professional Researchers? A Comparison of Professional Doctorate and PhD Programs in Criminology & Criminal Justice - Schildkraut, Jaclyn (American journal of criminal justice, 2015)
There are many questions asked by people who are thinking of entering a PhD program in criminology or criminal justice (CCJ). In addition to standard questions about completion time and assistantships, working professionals sometimes ask questions unique to them, such as whether a PhD will help them to obtain positions as upper-level administrators in law enforcement or why is it necessary to learn research skills. These questions take on added significance today because of the emergence of “professional doctorate programs.” This paper examines differences between professional doctorate and PhD programs in CCJ, with special emphasis on differences in research training and practical experience. This examination suggests that unlike other disciplines, the professional doctorate in CCJ is seen as a complementary degree to the PhD, designed to attract working professionals in the field to higher education, rather than as a competing degree as in other disciplines.